Marxist foundation and historical development: interpretation and practice in China’s new era - Meixu Chen (Trans/Form/Ação)
Professor Chen Xianda’s required course of Marxist Philosophy in the new era interprets the theory of socialism with Chinese characteristics in the new era theoretically, and tells people the Marxist philosophical basis of the theory of socialism with Chinese characteristics in the new era in a simple way. He wants to teach people to comprehensively and deeply understand the theory of socialism with new era characteristics on the basis of reading the original, learning it and understanding the principles, so as to better lead the practice. Among them, “learning to understand” requires leading cadres to accurately understand the logic system and theoretical origin of the socialist theory in the new era, and to enter the mind into the heart into the action. “Getting through” requires leading cadres to accurately grasp the theoretical logic, the historical one and practical logic of the thought in the new era, and to learn to examine the problems faced in the process of socialist construction from the perspective of the whole and development. “Being realistic” is required that the theory of leading cadres should be combined with practice, and the socialist thought, with Chinese characteristics in the new era, should be carried out and implemented in the specific work of this region and this department.